Perceptions and attitudes with regard to public international law: empirical evidence from law students in the city of São Paulo - Kamiyama, Marcel (Revista de Estudos Empíricos em Direito, 2017)
This article empirically examines, by means of a survey conducted at four universities in São Paulo, two issues related to the teaching of international law in Brazil: (1) what law students think of the discipline as a material branch of the law (its effectiveness, legitimacy etc.) and (2) what they think of the discipline as a component of the law school curriculum. The first part draws upon the semiological concept of “myth” in order to paint a picture of students’ views about the place of international law in the world, as well as upon quantitative data to assess their understandings about compliance with international norms. The second part, which also relies on quantitative and qualitative data, describes students’ ideas about how international law should be taught (if at all). The responses paint a picture of mild student scepticism and dissatisfaction with teaching methods that invite a number of questions for reflection, which are raised in the final part.